The Microsoft 2016 Conversational Speech Recognition System - Xiong, Wayne; Droppo, Jasha; Huang, Xuedong; Seide, Frank; Seltzer, Mike; Stolcke, Andreas; Yu, Dong; Zweig, Geoffrey (Proc. IEEE ICASSP, 2017)
We describe Microsoft’s conversational speech recognition system, in which we combine recent developments in neural-network-based acoustic and language modeling to advance the state of the art on the Switchboard recognition task. Inspired by machine learning ensemble techniques, the system uses a range of convolutional and recurrent neural networks. I-vector modeling and lattice-free MMI training provide significant gains for all acoustic model architectures. Language model rescoring with multiple forward and backward running RNNLMs, and word posterior-based system combination provide a 20% boost. The best single system uses a ResNet architecture acoustic model with RNNLM rescoring, and achieves a word error rate of 6.9% on the NIST 2000 Switchboard task. The combined system has an error rate of 6.2%, representing an improvement over previously reported results on this benchmark task.